The Meaning of Ephesians Competing Christianities in Second-Century Ephesus - Lollar, Jacob (2025)
The reception history of Ephesians presents many difficulties fundamentally related to the textual variant in Eph 1:1. The lack of an address to the letter destabilizes the connection that the letter has to the city of Ephesus. The earliest references to the letter in the second century show that the link between the epistle and the city was not obvious. This article offers a proposal for how Ephesians and Ephesus became tied to one another. Ephesian Christians claimed their foundations went back to either Paul or John. The earliest texts (e.g., Acts and the Acts of John) disagree about who evangelized the city first. Ambiguity regarding Ephesus’s conversion continued as late as the fifth century. This article argues that the address to Ephesus was added to an otherwise general letter in the Pauline corpus to legitimize claims that Paul was the first evangelist to the city of Ephesus.
Keywords: Patristics; Reception History; Acts of John; Acts; John; Paul; Ephesus; Ephesians